Heat treatment method for improving strength and plasticity of SLM formed ODS-RAFM steel

By normalizing and carbon-distribution heat treatment of SLM-formed ODS-RAFM steel, the problem of insufficient strong plasticity is solved, the strength and plasticity of the material are significantly improved, and its application ability under extreme conditions is enhanced.

CN119407204APending Publication Date: 2025-02-11HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411560666.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

SLM-formed ODS-RAFM steel is insufficient in extreme conditions, resulting in an increased risk of brittle fracture, affecting the reliability of the fusion reactor cladding.

Method used

Parts are manufactured through powder bed melting technology using ODS-RAFM steel powder, and normalized heat treatment and carbon distribution heat treatment are carried out. The normalization treatment temperature is 1050-1100℃, and the heat treatment temperature is kept at 1 hour, and then air-cooled to room temperature; the heat treatment temperature of carbon partition is 450-550℃, and the heat treatment temperature is kept at 3 to 5 minutes, and the water-cooled mode is used to cool to room temperature.

Benefits of technology

By eliminating columnar crystal structure and forming transition carbide precipitation phases, the strength and plasticity of ODS-RAFM steel are improved, the anisotropy of tensile properties is reduced, and the overall performance of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119407204A_ABST
    Figure CN119407204A_ABST
Patent Text Reader

Abstract

The invention discloses a heat treatment method for improving the strength and plasticity of SLM formed ODS-RAFM steel, and belongs to the field of additive manufacturing ODS-RAFM steel. The invention relates to a heat treatment method for improving the strength and plasticity of SLM formed ODS-RAFM steel. The heat treatment method comprises the steps that ODS-RAFM steel powder is adopted, and an ODS-RAFM steel part is manufactured through a powder bed melting technology; the obtained ODS-RAFM steel part is sequentially subjected to normalizing heat treatment and carbon distribution heat treatment; normalizing treatment is conducted on the sedimentary-state ODS-RAFM steel, a columnar crystal structure formed in the rapid solidification process is eliminated, and a ferrite and martensite mixed microstructure is obtained; then, carbon distribution heat treatment is adopted, and a transitional carbide precipitated phase is obtained; through dispersion strengthening generated by forming two precipitated phases in a matrix, fine grain strengthening and dislocation strengthening of a quenched structure and solid solution strengthening of part of alloy elements, the strength and plasticity of the ODS-RAFM steel are jointly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of additively manufactured ODS-RAFM steel, and in particular relates to a heat treatment method for improving the strength and plasticity of SLM formed ODS-RAFM steel. Background Art

[0002] The blanket components are the key functional areas for heat generation, heat exchange and shielding in fusion reactors. The blanket structural materials need to work for a long time in extremely high temperature and strong radiation environments. Under such conditions, the materials may experience repeated thermal cycles and radiation damage. If the plasticity of the materials is insufficient, brittle fracture or irreversible deformation may occur, affecting the integrity and function of the blanket. Therefore, the blanket structural materials are required to have good strength and plasticity to ensure that after being subjected to certain stresses and strains during service, the stability and reliability of the structure can be maintained for a long time, thereby ensuring the safe operation of the fusion reactor.

[0003] At present, nano-oxide dispersion strengthened low-activation ferrite / martensite (ODS-RAFM) steel has attracted much attention due to its excellent high-temperature performance, radiation damage resistance and low activation characteristics, and is considered to be the best candidate structural material for fusion reactor blanket. However, the complex structure of the blanket poses great challenges to both manufacturing technology and material properties. Additive manufacturing technology represented by selective laser melting (SLM) can achieve the production of complex geometric shapes. Although SLM manufacturing of ODS-RAFM steel can significantly improve production efficiency and design flexibility, printing ODS-RAFM steel still has prominent problems such as strength-plasticity mismatch and anisotropy of mechanical properties. Specifically, the columnar crystals formed during the printing process and the random defects that may be formed lead to insufficient plasticity of the material in local areas, increasing the risk of brittle fracture. The lack of strength and plasticity not only limits the application of ODS-RAFM steel under extreme conditions, but also may affect the overall reliability of the blanket. Therefore, appropriate heat treatment is required to regulate the non-equilibrium solidification structure and improve the mechanical properties of ODS-RAFM steel.

[0004] At present, the heat treatment process for ODS-RAFM steel mainly includes normalizing, tempering, quenching and annealing. Usually, normalizing and quenching are to keep the steel above the austenite transformation end temperature (Ac3) for a period of time, and then cool it to room temperature by air cooling and water cooling. For tempering and annealing, it is usually kept below the austenite transformation start temperature (Ac1) for a certain period of time, and the internal stress of quenching is reduced and the plasticity of ODS-RAFM steel is restored by air cooling. Therefore, in order to further expand the application scope of SLM-formed ODS-RAFM steel, it is urgent to develop a heat treatment scheme suitable for additive manufacturing of ODS-RAFM steel to improve the strength and plasticity of ODS-RAFM steel to ensure that it can meet the high requirements of fusion reactor blanket for structural materials. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel, thereby solving the problems in the prior art.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel, comprising the following steps:

[0008] Using ODS-RAFM steel powder, ODS-RAFM steel parts are manufactured using powder bed fusion technology;

[0009] The obtained ODS-RAFM steel parts were subjected to normalizing heat treatment and carbon partitioning heat treatment in sequence.

[0010] Furthermore, the ODS-RAFM steel parts are manufactured using FS271M equipment, and its printing process parameters are: laser power 360-400W, scanning speed 600-800mm / s, overlap spacing 80-90μm, and layer thickness 30μm.

[0011] Furthermore, the scanning mode of printing is Zigzag.

[0012] Furthermore, the normalizing heat treatment temperature is 1050-1100° C. and the heat preservation time is 1 hour.

[0013] Furthermore, during the normalizing heat treatment process, air cooling mode is adopted to cool to room temperature.

[0014] Furthermore, the carbon distribution heat treatment temperature is 450-550° C., and the insulation time is 3-5 minutes.

[0015] Furthermore, during the carbon distribution heat treatment process, a water cooling mode is used to cool to room temperature.

[0016] Furthermore, the preparation process of ODS-RAFM steel powder includes:

[0017] Step 1: According to the composition of RAFM steel, gas atomization powder making technology is used to uniformly melt in an inert gas protection atmosphere, and then under the action of pressure, the metal droplets are broken and solidified into RAFM steel powder;

[0018] Step 2: Dissolve a plurality of pre-designed soluble inorganic salt hydrates as precursors in a solvent, and then mix them evenly to form a sol, and undergo hydrolysis and polycondensation reactions to form a nanoscale multi-nanophase; then adjust the pH and temperature to form a gel, and finally calcine to obtain a multi-nanooxide.

[0019] Step 3, using electrostatic adsorption technology to introduce multi-element nano-oxides into RAFM steel powder to prepare ODS-RAFM steel powder;

[0020] Furthermore, the specific process of step 3 is: using a surfactant to disperse multi-element nano-oxides in a C2H5OH solution, and then adding NH3·H2O to adjust the solution to be weakly alkaline; dispersing RAFM steel powder in a C2H5OH solution, and using HCl to adjust the solution to be weakly alkaline; then mixing the above two solutions and stirring, and finally drying to form the ODS-RAFM steel powder to be used.

[0021] Furthermore, in the ODS-RAFM steel powder, the added mass fraction of the multi-component nano-oxide is 0.6-1.0%.

[0022] An ODS-RAFM steel component is obtained by using the above-mentioned heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel.

[0023] Beneficial effects of the present invention:

[0024] 1. The present invention normalizes the ODS-RAFM steel to eliminate the columnar crystal structure formed in the deposition state and obtain a mixed microstructure of ferrite and martensite; then obtains a transitional carbide precipitation phase through carbon distribution heat treatment; and realizes ODS-RAFM steel with improved strength and plasticity through dispersion strengthening of two precipitated phases formed in the matrix, fine grain strengthening and dislocation strengthening of the quenched structure, and solid solution strengthening of some alloys.

[0025] 2. The present invention adopts the sol-gel method to prepare multi-element nano-oxides, and while obtaining nano-scale oxide particles, it also prepares nano-phases with better thermal stability, slowing down the coarsening rate of nano-particles in the laser molten pool.

[0026] 3. The present invention uses electrostatic adsorption technology to introduce multi-element nano-oxide powders onto the surface of RAFM steel powders, with the aim of not destroying the sphericity of the RAFM steel matrix powders manufactured by gas atomization, thereby obtaining high-fluidity ODS-RAFM steel powders, providing high-quality raw material powders for suppressing the formation of printing defects.

[0027] 4. The normalizing temperature and time adopted by the present invention can fully ensure the disappearance of the columnar crystal structure formed in the deposition state, and obtain a normalized structure with a ferrite and martensite structure ratio close to 1:1. Generating a certain amount of ferrite structure is conducive to the diffusion of supersaturated carbon elements in the martensite structure into the ferrite to form transitional carbides during the carbon distribution process.

[0028] 5. The carbon distribution heat treatment temperature adopted in the present invention is moderate. If the temperature is too low, the diffusion and precipitation of carbon atoms are hindered and transitional carbides cannot be formed; if the temperature is too high, the size of the carbon atom precipitation phase grows rapidly, which is not conducive to the improvement of strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 The microstructure morphology of the deposited ODS-RAFM steel in Example 1 is shown in side view and top view;

[0031] Figure 2 The microstructure morphology of the normalized + carbon distribution state ODS-RAFM steel in Example 1;

[0032] Figure 3 TEM microstructure of the deposited ODS-RAFM steel in Example 1;

[0033] Figure 4 This is the TEM microstructure of the normalized + carbon partitioned ODS-RAFM steel in Example 1;

[0034] Figure 5 The engineering stress-engineering strain curves of samples of the deposited ODS-RAFM steel in Example 1 at room temperature and 700°C in different test directions;

[0035] Figure 6 The engineering stress-engineering strain curves of the carbon-distributed ODS-RAFM steel samples in different test directions at room temperature and 700°C high temperature in Example 1;

[0036] Figure 7 The microstructure morphology of the deposited ODS-RAFM steel in Example 2 is shown in side view and top view;

[0037] Figure 8 The microstructure morphology of the normalized + carbon distribution state ODS-RAFM steel in Example 2;

[0038] Fig. 9 TEM microstructure of the deposited ODS-RAFM steel in Example 2;

[0039] Fig.10 This is the TEM microstructure of the normalized + carbon partitioned ODS-RAFM steel in Example 2;

[0040] Fig.11The engineering stress-engineering strain curves of the deposited and carbon-distributed ODS-RAFM steel samples in different test directions at room temperature in Example 2;

[0041] Fig.12 The microstructure morphology of the normalized + tempered ODS-RAFM steel in Comparative Example 1;

[0042] Fig.13 TEM microstructure of the normalized + tempered ODS-RAFM steel in Comparative Example 1;

[0043] Fig.14 The engineering stress-engineering strain curves of samples of normalized + tempered ODS-RAFM steel in comparative example 1 at room temperature and 700°C in different test directions. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The steps for preparing ODS-RAFM steel powder are:

[0046] (1) RAFM steel powder was prepared by gas atomization powder making technology;

[0047] According to the standard composition of RAFM steel (Fe-9Cr-1.5W-0.45Mn-0.2V-0.15Ta-0.1C), gas atomization powder making technology is used to evenly melt in an inert gas protection atmosphere. Then, under the action of gas pressure, the metal droplets are broken and solidified into fine RAFM steel powder, and the powder of 15-53μm is screened for standby use;

[0048] (2) manufacturing multi-element nano-oxide phases;

[0049] Select suitable soluble inorganic salt water compounds (such as zirconium nitrate pentahydrate (Zr(NO3)4·5H2O), yttrium nitrate hexahydrate (Y(NO3)3·6H2O), titanium nitrate pentahydrate (Ti(NO3)4·5H2O)) as precursors, and dissolve them in appropriate solvents (such as stearic acid (C 18 H 36 O2), oleic acid (C 18 H 34O2), cyclohexane (Cyclohexane), etc.), and then mix the formed sol evenly, and undergo hydrolysis and polycondensation reactions to form nanoscale multi-nanophases; then adjust the pH and temperature to form a gel, keep the temperature for a certain period of time to promote the growth of the nanophase and the discharge of the solvent, and finally calcine to obtain multi-nanooxides (such as: Y4Zr3O 12 , Y2Ti2O7, Y2TiO5, Y2SiO5, etc.) strengthening phase.

[0050] (3) electrostatic adsorption technology was used to introduce multi-element nano-oxides into RAFM steel powder to prepare ODS-RAFM steel powder;

[0051] The specific process is as follows: using a surfactant to disperse multi-element nano-oxides in a C2H5OH solution, and then adding NH3·H2O to adjust the solution to be weakly alkaline; dispersing RAFM steel powder in a C2H5OH solution, and using HCl to adjust the solution to be weakly alkaline; then mixing the above two solutions and stirring, and finally drying to form the ODS-RAFM steel powder to be used.

[0052] Among them, in the ODS-RAFM steel powder, the added mass fraction of the multi-element nano-oxide is 0.6-1.0%, and the mass fraction of the RAFM steel powder is 99.4-99.0%.

[0053] The ODS-RAFM steel powder preparation technology adopted in the present invention can obtain nano-scale dispersed oxide particles in the matrix; however, the non-equilibrium solidification structure formed under rapid solidification affects the anisotropy and strong plasticity of the ODS-RAFM steel. For this purpose, the following heat treatment method is proposed:

[0054] A heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel, comprising the following steps:

[0055] S1, using ODS-RAFM steel powder and powder bed fusion technology to manufacture ODS-RAFM steel parts;

[0056] The FS271M equipment is used to manufacture ODS-RAFM steel parts, and its printing process parameters are: laser power 360-400W, scanning speed 600-800mm / s, overlap spacing 80-90μm, layer thickness 30μm, substrate preheating temperature 100℃, and Zigzag scanning mode.

[0057] S2, the obtained ODS-RAFM steel parts are subjected to normalizing heat treatment and carbon distribution heat treatment in sequence.

[0058] The normalizing heat treatment temperature is 1050-1100°C, kept at this temperature for 1 hour, and cooled to room temperature by air cooling mode; during the normalizing heat treatment process, the ODS-RAFM steel parts are placed after the furnace temperature rises to the set temperature.

[0059] The carbon distribution heat treatment temperature is 450-550°C, the holding time is 3-5 minutes, and the water cooling mode is used to cool to room temperature; during the carbon distribution heat treatment process, the ODS-RAFM steel parts are placed after the furnace temperature rises to the set temperature.

[0060] Through normalizing treatment, the columnar crystal structure formed in the deposition state is eliminated and a mixed microstructure of ferrite and martensite is obtained; then, through carbon distribution heat treatment, a transitional carbide precipitation phase is obtained. Through the dispersion strengthening of the two precipitation phases formed in the matrix, the fine grain strengthening and dislocation strengthening of the quenched structure, and the solid solution strengthening of some alloys, ODS-RAFM steel with improved strength and plasticity is achieved.

[0061] Example 1

[0062] In this embodiment, normalizing + carbon distribution heat treatment is used to optimize the microstructure and tensile properties of ODS-RAFM steel; the specific steps are:

[0063] S1, designed Y4Zr3O 12 Multi-element nano-oxide phase-reinforced RAFM steel powder was machined using FS271M equipment with a laser power of 400W, a scanning speed of 600mm / s, an overlap spacing of 80μm, a layer thickness of 30μm, and a laser energy density of 277J / mm 3 Three groups of ODS-RAFM steel samples with a length of 100 mm, a width of 12 mm, and a height of 65 mm were prepared. The samples without any treatment after printing were referred to as the deposited state.

[0064] S2, the samples obtained in S1 are subjected to normalizing + carbon distribution heat treatment, and the specific parameters are as follows: the temperature is raised to 1100°C, and then the samples are placed in and kept warm for 1 hour, and then the samples are taken out and air-cooled to room temperature; the temperature is raised to 550°C again, and then the normalized and air-cooled samples are placed in and kept warm for 3 minutes, and then the samples are taken out and water-cooled to room temperature. The samples after carbon distribution treatment are referred to as carbon distribution state.

[0065] The microstructure of the deposited sample obtained in S1 was observed, and the results are as follows: Figure 1 shown. Figure 1 (a) and (b) in the figure show the microstructure of the deposited sample in the side view and top view, respectively. It can be seen that the microstructure is obviously different in different observation directions; along the printing direction, there are obvious columnar crystals, and the existence of columnar crystals is the fundamental reason for the anisotropy of mechanical properties.

[0066] The microstructure of the normalized + carbon distribution state sample obtained by S2 was observed, and the results are as follows Figure 2 As shown in Figure 2, it can be found that the coarse columnar grains formed in the deposition state disappear, and the original austenite grain structure with equal size in all directions is obtained.

[0067] The microstructure of the deposited sample in S1 was observed by transmission electron microscopy. Figure 3 shown. Figure 3 (a) and (b) are the side view and top view respectively. It can be seen that the microstructure is composed of large ferrite grains and martensite laths, and a large amount of Y4Zr3O is distributed in the matrix. 12 Multinary nano-oxide particles.

[0068] The microstructure of the normalized + carbon distribution state sample obtained in S2 was observed by transmission electron microscopy. The results are as follows: Figure 4 As shown. It can be seen that in the bainite structure area, Figure 4 As shown in (a), in addition to the existing Y4Zr3O 12 In addition to the multi-element nano-oxides, a certain amount of elongated θ-carbides were also precipitated, with a length of about 154±23.9nm and a width of about 18.6±4.23nm. In the quenched martensite structure area, such as Figure 4 As shown in (b), the martensite laths are obviously refined, and there is a certain amount of Y4Zr3O 12 Multi-element nano-oxides.

[0069] The room temperature tensile properties of the deposited samples in S1 at 0°, 45° and 90° directions and the high temperature tensile properties at 700°C were tested. The engineering stress-engineering strain curves are shown in Figure 5 As shown. It can be seen that there are obvious differences in tensile strength and elongation in different directions. Especially in the test results in the 90° direction, the tensile strength at room temperature and high temperature is low. Figure 5 As shown in (a) in the figure, the total elongation at room temperature is 12.2±2.31%, the uniform elongation is 7.6±1.89%, the yield strength is 851±6.6MPa, and the tensile strength is 1127±15.9MPa. The IPA of the total elongation, yield strength, and tensile strength are 12.78, 1.68, and 2.92, respectively. Figure 5 As shown in (b), the total elongation at 700°C is 10.9±2.39%, the yield strength is 475±31.3MPa, and the tensile strength is 521±26.5MPa. The IPA of the total elongation, yield strength, and tensile strength are 7.81, 9.76, and 10.64, respectively.

[0070] The room temperature tensile properties of the normalized + carbon distribution samples obtained in S2 at 0°, 45° and 90° directions and the high temperature tensile properties at 700°C were tested. The engineering stress-engineering strain curves are shown in Figure 6 As shown. It can be seen that compared with the deposited state, the anisotropy of tensile strength and elongation in different directions at room temperature has been significantly improved, and both strength and elongation have been improved to a certain extent. For high-temperature tensile properties, the tensile strength in different directions is relatively consistent, and the elongation is slightly different. Figure 6 As shown in (a) in the figure, the total elongation at room temperature is 13.8±0.27%, the uniform elongation is 8.7±0.34%, the yield strength is 986±8.9MPa, and the tensile strength is 1214±9.2MPa. The IPA of the total elongation, yield strength, and tensile strength are 2.41, 0.57, and 1.31, respectively. Figure 6 As shown in (b), the total elongation at 700°C is 15.8±2.24%, the yield strength is 540±8.2MPa, and the tensile strength is 581±6.4MPa. The IPA of the total elongation, yield strength, and tensile strength are 8.36, 1.51, and 1.86, respectively.

[0071] In summary, at room temperature, the total elongation, uniform elongation, yield strength and tensile strength in S2 increased by 11.5%, 12.6%, 13.7% and 7.2% respectively compared with the as-deposited samples; the elongation, yield strength and tensile strength of IPA decreased by 81.1%, 66.0% and 55.1% respectively.

[0072] At 700℃, the total elongation, yield strength and tensile strength of S2 increased by 31.0%, 12.0% and 10.3% respectively compared with the deposited samples; the IPA of total elongation, yield strength and tensile strength decreased by 7.04%, 84.5% and 82.3 respectively. It can be seen that S2 significantly reduced the anisotropy of the tensile properties of the deposited state, and the strength and plasticity were improved to a certain extent.

[0073] Example 2

[0074] In this embodiment, normalizing + carbon distribution heat treatment is used to optimize the microstructure and tensile properties of ODS-RAFM steel; the specific steps are:

[0075] S3, designed Y4Zr3O 12 Multi-element nano-oxide phase-reinforced RAFM steel powder was machined using FS271M equipment with a laser power of 360W, a scanning speed of 800mm / s, an overlap spacing of 90μm, a layer thickness of 30μm, and a laser energy density of 166J / mm 3Three groups of ODS-RAFM steel samples with a length of 100 mm, a width of 12 mm, and a height of 65 mm were prepared. The samples without any treatment after printing were referred to as the deposited state.

[0076] S4, the samples obtained in S3 are subjected to normalizing + carbon distribution heat treatment, and the specific parameters are as follows: the temperature is raised to 1050°C, and then the samples are placed in and kept warm for 1 hour, and then the samples are taken out and air-cooled to room temperature; the temperature is raised to 450°C again, and then the samples that have been air-cooled after normalizing are placed in and kept warm for 5 minutes, and then the samples are taken out and water-cooled to room temperature. The samples after carbon distribution treatment are referred to as carbon distribution state.

[0077] The microstructure of the deposited sample obtained in S3 was observed, and the results are as follows: Figure 7 shown. Figure 7 (a) and (b) in the figure show the microstructure of the deposited sample in the side view and top view, respectively. It can also be seen that the microstructure is obviously different in different observation directions; along the printing direction, there is a certain amount of columnar crystal structure, and the existence of columnar crystal is the fundamental reason for the anisotropy of mechanical properties.

[0078] The microstructure of the normalized + carbon distribution state sample obtained by S4 was observed, and the results are as follows Figure 8 It can also be found that the columnar crystals in the deposited state disappear, and the original austenite grain structure with equal size in all directions is obtained.

[0079] The microstructure of the deposited sample in S3 was observed by transmission electron microscopy. Fig. 9 shown. Fig. 9 (a) and (b) are the side view and top view respectively. It can be seen that the microstructure is composed of large ferrite grains and martensite laths, and a certain amount of Y4Zr3O is distributed in the matrix. 12 Multinary nano-oxide particles.

[0080] The microstructure of the normalized + carbon distribution sample obtained in S4 was observed by transmission electron microscopy. Fig.10 As shown. It can be seen that in the bainite structure area, Fig.10 As shown in (a), the aspect ratio of the elongated θ-carbide precipitate phase is significantly reduced, with a length of about 86±11.5nm and a width of about 13.8±2.24nm. In the quenched martensite structure area, such as Fig.10 As shown in (b), the martensite laths are relatively thin and contain a certain amount of Y4Zr3O 12 Multi-element nano-oxides.

[0081] The room temperature tensile properties of the deposited samples in S3 at 0°, 45° and 90° directions were tested, and the engineering stress-engineering strain curves are shown in Fig.11(a) As shown. The total elongation of the deposited sample under this parameter at room temperature is 11.7±2.45%, the uniform elongation is 7.1±2.13%, the yield strength is 832±7.5MPa, and the tensile strength is 1028±17.2MPa. The IPA of total elongation, yield strength and tensile strength are 14.21, 1.84 and 3.15 respectively. There is obvious anisotropy.

[0082] The room temperature tensile properties of the normalized + carbon distribution samples obtained in S4 at 0°, 45° and 90° directions were tested, and the engineering stress-engineering strain curves are shown in Fig.11 (b) The total elongation at room temperature is 12.4±0.35%, the uniform elongation is 7.8±0.39%, the yield strength is 947±9.8MPa, and the tensile strength is 1114±10.6MPa. The IPA of elongation, yield strength, and tensile strength are 3.96, 0.97, and 1.43, respectively.

[0083] In summary, at room temperature, the total elongation, uniform elongation, yield strength and tensile strength of S2 increased by 6.0%, 9.8%, 12.4% and 8.3% respectively compared with the deposited samples; the IPA of elongation, yield strength and tensile strength decreased by 72.1%, 47.2% and 54.6% respectively. It can be seen that S2 significantly reduced the anisotropy of the tensile properties of the deposited state, and the strength and plasticity were improved to a certain extent.

[0084] Comparative Example 1

[0085] In this comparative example, normalizing + tempering was used to treat ODS-RAFM steel; the specific steps were:

[0086] S1, designed Y4Zr3O 12 The multi-element nano-oxide phase-reinforced RAFM steel powder was prepared using FS271M equipment with a laser power of 400W, a scanning speed of 600mm / s, an overlap spacing of 80μm, and a layer thickness of 30μm. Three groups of ODS-RAFM steel samples with a length of 100mm, a width of 12mm, and a height of 65mm were prepared. The samples that were not processed after printing were referred to as deposited states.

[0087] S2, the samples obtained in S1 were subjected to normalizing + tempering heat treatment, and the specific parameters were as follows: the temperature was raised to 980°C, and then the samples were placed in and kept warm for 0.5h, and then the samples were taken out and air-cooled to room temperature; the temperature was raised to 760°C again, and then the samples that were air-cooled after normalizing were placed in and kept warm for 1.5h, and then the samples were taken out and air-cooled to room temperature. The samples after normalizing + tempering treatment are referred to as tempered state.

[0088] The microstructure of the normalized + tempered sample obtained in Comparative Example S2 was observed, and the results are as follows: Fig.12 As shown in Figure 2, after normalizing and tempering heat treatment, the coarse columnar crystal structure in the deposited state was also alleviated, and the original austenite grain structure with equal size in all directions was obtained.

[0089] The microstructure of S1 after treatment was observed by transmission electron microscopy. Fig.13 As shown. Fig.13 As shown in (a), a large number of M 23 C6 and MX type precipitation phases. Fig.13 As shown in (b), there are also microstructures composed of various different types of precipitated phases inside the grains.

[0090] The room temperature tensile properties of the normalized + tempered samples in the directions of 0°, 45° and 90° and the high temperature tensile properties at 700°C were tested. The engineering stress-engineering strain curves are shown in Fig.14 As shown. Fig.14 As shown in (a), compared with the deposited state, the anisotropy of tensile strength and elongation in different directions at room temperature has been improved after normalizing + tempering treatment. Although the elongation has increased, the strength has decreased significantly. The total elongation at room temperature is 16.3±0.36%, the uniform elongation is 8.5±0.42%, the yield strength is 582±2.7MPa, and the tensile strength is 708±4.7MPa. The IPA of elongation, yield strength and tensile strength are 2.72, 0.63 and 1.39, respectively. Fig.14 As shown in (b), the total elongation at 700°C is 27.4±1.57%, the yield strength is 227±6.1MPa, and the tensile strength is 264±6.3MPa. The IPA of elongation, yield strength, and tensile strength are 8.25, 5.28, and 4.74, respectively.

[0091] In summary, at room temperature, the total elongation, uniform elongation, yield strength and tensile strength of the normalized + tempered samples obtained in the comparative example increased by 15.3% compared with the samples in the carbon distribution state, but the uniform elongation, yield strength and tensile strength decreased by 2.3%, 40.9% and 41.7%, respectively. The IPA of elongation, yield strength and tensile strength increased by 11.4%, 9.5% and 5.8%, respectively. At a high temperature of 700°C, the elongation, yield strength and tensile strength of the normalized + tempered samples obtained in the comparative example increased by 42.3% compared with the samples in the carbon distribution state, but the yield strength and tensile strength decreased by 57.9% and 54.6%, respectively. The IPA of elongation, yield strength and tensile strength increased by 8.36, 1.51 and 1.86, respectively. It can be seen that although the comparative treatment method (normalizing + tempering) can also reduce the anisotropy of tensile properties, the strength and plasticity are significantly reduced.

[0092] The tensile properties of the ODS-RAFM steel in the deposited state, carbon distribution state and comparative tempered state in the embodiment are summarized. Table 1 and Table 2 are the test results of the tensile properties at room temperature and 700°C respectively. To further clarify the strengthening mechanism, Table 3 summarizes the statistical data results of the grain size, dislocation density and precipitation phase type of the ODS-RAFM steel in different states. Table 4 gives the contribution values ​​of each strengthening mechanism to the yield strength in different states in the embodiment and comparative example.

[0093] Table 1 Room temperature tensile properties of ODS-RAFM steel in the examples and comparative examples

[0094]

[0095] Table 2 High temperature tensile properties of ODS-RAFM steel in the examples and comparative examples

[0096]

[0097] Table 3 Data values ​​of improving yield strength of ODS-RAFM steel in different states under the embodiments and comparative examples

[0098]

[0099] Table 4 Contribution of different strengthening mechanisms of ODS-RAFM steel to yield strength in the examples and comparative examples

[0100]

[0101] It can be seen that the carbon distribution state effectively improves the strength of ODS-RAFM steel and obtains better plasticity.

[0102] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0103] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel, characterized in that: The following steps are involved: Using ODS-RAFM steel powder, ODS-RAFM steel parts are manufactured using powder bed fusion technology; The obtained ODS-RAFM steel parts were subjected to normalizing heat treatment and carbon partitioning heat treatment in sequence.

2. A heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel according to claim 1, characterized in that: The ODS-RAFM steel parts are manufactured using FS271M equipment, and the printing process parameters are: laser power 360-400W, scanning speed 600-800mm / s, overlap spacing 80-90μm, and layer thickness 30μm.

3. A heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel according to claim 2, characterized in that: The printed scan pattern is Zigzag.

4. A heat treatment method for improving the strength and plasticity of SLM formed ODS-RAFM steel according to claim 1, characterized in that: The normalizing heat treatment temperature is 1050-1100° C. and the heat preservation time is 1 hour.

5. A heat treatment method for improving the strength and plasticity of SLM formed ODS-RAFM steel according to claim 4, characterized in that: During the normalizing heat treatment process, air cooling mode is used to cool to room temperature.

6. A heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel according to claim 1, characterized in that: The carbon distribution heat treatment temperature is 450-550° C., and the heat preservation time is 3-5 minutes.

7. A heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel according to claim 6, characterized in that: During the carbon distribution heat treatment, water cooling mode was used to cool to room temperature.

8. A heat treatment method for improving the strength and plasticity of SLM formed ODS-RAFM steel according to claim 1, characterized in that: The preparation process of ODS-RAFM steel powder includes: Step 1: According to the composition of RAFM steel, gas atomization powder making technology is used to uniformly melt in an inert gas protection atmosphere, and then under the action of pressure, the metal droplets are broken and solidified into RAFM steel powder; Step 2, using a plurality of pre-designed soluble inorganic salt hydrates as precursors, dissolving them in a solvent, and then mixing them to form a sol, and causing hydrolysis and polycondensation reactions to form a nanoscale multi-nano phase; then adjusting the pH and temperature to form a gel, and finally calcining to obtain a multi-nano oxide; Step 3, using electrostatic adsorption technology to introduce multi-element nano-oxides into RAFM steel powder to prepare ODS-RAFM steel powder; The specific process of step 3 is: using a surfactant to disperse multi-element nano-oxides in a C2H5OH solution, and then adding NH3·H2O to adjust the solution to be weakly alkaline; dispersing RAFM steel powder in the C2H5OH solution, and using HCl to adjust the solution to be weakly alkaline; then mixing the above two solutions and stirring, and finally drying to form the ODS-RAFM steel powder to be used.

9. A heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel according to claim 8, characterized in that: In the ODS-RAFM steel powder, the added mass fraction of multi-component nano-oxides is 0.6-1.0%.

10. An ODS-RAFM steel component, characterized in that: The steel is obtained by using a heat treatment method for improving the strength and plasticity of SLM-formed ODS-RAFM steel as described in any one of claims 1 to 9.

Citation Information

Cited By

  • Oxide dispersion strengthened RAFM steel as well as preparation method and application thereof

    CN120243978A

  • Oxide dispersion strengthened RAFM steel and its preparation method and application

    CN120243978B